2011
DOI: 10.1007/s10753-011-9309-5
|View full text |Cite
|
Sign up to set email alerts
|

PI3-Kinase Regulates Eosinophil and Neutrophil Degranulation in Patients with Allergic Rhinitis and Allergic Asthma Irrespective of Allergen Challenge Model

Abstract: The PI3K pathway plays a major role in many vital cell processes. Our primary aim was to investigate signalling through PI3K for in vitro degranulation from allergen-primed eosinophils and neutrophils in allergic rhinitis and allergic asthma after seasonal and experimental allergen challenge. Nine patients with allergic rhinitis, eight with allergic asthma and four controls were studied during birch pollen season and after nasal and bronchial allergen challenge. Primed blood eosinophils and neutrophils were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…46,47 The majority of the miRNA groups also target the phosphoinositide 3-kinase-Akt pathway, which is another particularly well-studied signaling cascade in T H 2 inflammation. 48,49 Furthermore, there is emerging evidence in the literature that implicates neurotrophin 50,51 and insulin signaling in patients with allergic lung diseases. 52 Focal adhesion pathways targeted by group 2 and 3 miRNAs in our study are likely involved in changes in airway basement membrane and airway smooth muscle in asthmatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 The majority of the miRNA groups also target the phosphoinositide 3-kinase-Akt pathway, which is another particularly well-studied signaling cascade in T H 2 inflammation. 48,49 Furthermore, there is emerging evidence in the literature that implicates neurotrophin 50,51 and insulin signaling in patients with allergic lung diseases. 52 Focal adhesion pathways targeted by group 2 and 3 miRNAs in our study are likely involved in changes in airway basement membrane and airway smooth muscle in asthmatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…PI3Ks are thought to be involved in a number of pathological states such as cancer, inflammation and allergy. Studies also showed that PI3K pathway plays a crucial role in the pathogenesis of asthma (Kampe et al, 2012;Ro et al, 2013;Takeda et al, 2010). In vitro, PI3K was required for activation of caspase-1, secretion of IL-1b and IL-18, as well as nucleocytoplasmic translocation of HMGB1 (Oh et al, 2009;Tapia-Abellan et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Upon stimulation by chemotactic factors or chemokines, transmigrated eosinophils arrive in inflamed tissues and are further activated by the proinflammatory microenvironment, which leads to diverse cellular responses, such as adhesion to extracellular matrix proteins, neutrophils or T cells, degranulation and production of cytokines, chemokines or cysteinyl leukotrienes [22,23,24]. Among those responses, degranulation plays a direct role in eliciting eosinophil-mediated tissue inflammatory responses [25]. In particular, degranulation via granule exocytosis resulting from an intracellular granular membrane fusing with a plasma membrane facilitates innate immune responses by releasing cytotoxic granular proteins and preformed chemokines or cytokines, and by delivering reserved chemotactic factor receptors, integrins or adhesive molecules to the cell surface [26,27,28,29].…”
Section: Introductionmentioning
confidence: 99%